Making fully printed perovskite solar cells stable outdoor with inorganic superhydrophobic coating - Luo, Jianqiang (2022)
Outdoor environment including moisture, dust, UV, oxygen and thermal stress (repeated heating-cooling) is devastating to perovskite solar cells (PSCs). Here, we demonstrate a new strategy to make fully printed PSCs stable with maximum power output in outdoor environment by coating them with a porous hydrophobic inorganic layer. After coating, the PSCs can maintain superior stability of more than 150 days of outdoor storage, 240 h of continuous operation at the maximum power output point in ambient air with relative humidity as high as ~80%, and stable operation for more than 10 h under raining condition. ANSYS simulation shows that the thin and porous nature of the inorganic coating layer offers much better heat dissipation than conventional encapsulation methods using glasses attached by photocurable epoxy. A similar thermal expansion coefficient of the inorganic encapsulation material with the solar cell substrate can also prevent it from cracking after repeated heating-cooling cycles. All of these merits resulted from our encapsulation method endow the perovskite solar cells with the real outdoor working capability.